Wilson's disease: the 60th anniversary of Walshe's article on treatment with penicillamine - Teive, Hélio A. G.; Barbosa, Egberto Reis; Lees, Andrew J. (Arquivos de Neuro-Psiquiatria, 2017)
This historical review describes Professor Walshe's seminal contribution to the treatment of Wilson's disease on the 60th anniversary of his pioneering article on penicillamine, the first effective treatment for the condition.
Keywords: hepatolenticular degeneration; therapeutics; penicillamine